Importance of addressing malnutrition in cancer and implementation of a quality improvement project in a gastrointestinal cancer clinic. (2nd August 2021) - Levonyak, Nicholas S.; Hodges, Mary P.; Haaf, Nicole; Brown, Timothy J.; Hardy, Shelli; Mhoon, Verca; Kainthla, Radhika; Beg, Muhammad Shaalan; Kazmi, Syed M.
Abstract: Malnutrition is exceedingly common in cancer patients, with some of the highest rates seen in gastrointestinal (GI) malignancies. Malnutrition and cachexia in cancer patients is associated with worse quality of life, poor treatment tolerance, and increased morbidity and mortality. The importance of early recognition of malnutrition in cancer patients is key, and numerous screening tools have been validated to aid practitioners in this diagnosis. In this paper, we summarize the importance of identifying and managing malnutrition in GI cancer patients as well as its impact on clinical outcomes. We then focus on presenting our own novel quality improvement project that aims to expand access to dietitian services in a GI cancer clinic at a large safety‐net hospital system. Utilizing evidence‐based quality improvement methodologies including the Model for Improvement and Plan‐Do‐Study‐Act cycles, we increased the proportion of GI oncology patients seen by a dietitian from 5% to 20% from October 2018 to July 2019. In particular, we outline the challenges faced in the implementation process of a malnutrition screening tool built into the electronic medical record in an outpatient oncology clinic. We focus on the tool's ability to capture a greater number of patients with malnutrition and its clinical impact.